2006
DOI: 10.1177/0264550506060869
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn from Serious Incident Reports?

Abstract: This is an examination of 90 Serious Incident Reports (SIRs) which were generated in the London Probation Area between January 2002 and July 2003. The results showed that offenders assessed as high risk generated a disproportionately high number of SIRs, but equally serious incidents occurred across all risk bands.Interpretation of this is not straightforward; despite confirming considerable accuracy by Probation staff in identifying those most likely to inflict harm, it also demonstrates the limitations of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The evidence could be stacked up to show probation practitioners are really rather successful in this task. For instance, my own research (Ansbro 2006) found that although high-risk offenders occupied only 4% of the caseload at the time, offenders in that risk category produced a full quarter of a sample of serious further offences (SFOs). National probation service research (National Probation Service 2005) found a similar pattern, but as an example of the 'cup half empty, cup half full' principle, this is rarely reported as a ringing triumph for accuracy in risk prediction.…”
mentioning
confidence: 99%
“…The evidence could be stacked up to show probation practitioners are really rather successful in this task. For instance, my own research (Ansbro 2006) found that although high-risk offenders occupied only 4% of the caseload at the time, offenders in that risk category produced a full quarter of a sample of serious further offences (SFOs). National probation service research (National Probation Service 2005) found a similar pattern, but as an example of the 'cup half empty, cup half full' principle, this is rarely reported as a ringing triumph for accuracy in risk prediction.…”
mentioning
confidence: 99%
“…I am not arguing that we concede to this environment by persevering on an unsustainable course of rule tightening, failing to acknowledge the truth that ‘serious re-offending whilst under supervision is inevitable’ (Ansbro, 2006: 65). But practitioners must be given time for reflection, supervision and consultation in recognition of the challenging nature of the work they undertake, and the responsibilities they face.…”
Section: Introductionmentioning
confidence: 99%
“…This allocation of cases on the basis of tick-box risk assessments continues despite research by Ansbro (2006) and Craissati and Sindall (2009) showing that low/medium risk offenders can go on to commit serious further offences and that risk is a dynamic evolving phenomena. The predominance of 'tick-box' risk assessment tools such as OASys sustains management belief that risk assessment and the management of the majority of offenders on probation can be effectively undertaken by deskilled operatives.…”
mentioning
confidence: 99%